Apokalypse nå! En undersøkelse av antroposofiske konspirasjonsfortellinger (Aura: Journal for the Study of New Religions, 2025)
The article examines how Rudolf Steiner’s anthroposophy and apocalypticism have been interpreted by anthroposophists who were confronted with Nazism in the 1930s/40s, as well as the impact these ideas have had within recent conspiracy theories related to the coronavirus. The article examines Steiner’s theodicy and how it is linked to so-called “resistance beings” who are said to have infiltrated and still infiltrate politics and technology. Discussing the term “occult imprisonment”, I reflect on the extent to which conspiracy narratives based on Steiner’s anthroposophy and apocalypticism place anthroposophy outside of time, so that it appears as a peculiar, sectarian Bessewisser culture. This is contrasted with interpretations of anthroposophy that are more commensurable with established discourses in science and culture.